INVESTIGATION OF LOW SALINITY WATERFLOODING POTENTIAL IN SYNTHETIC SANDSTONE RESERVOIR - GADESA (NIM : 12213056), ALGERI
Low salinity waterflooding (LSWF) is an enhanced oil recovery (EOR) technique that has recently become attractive due to its relatively low cost, its simple operational design, and its low environmental impact. There are an increasing number of LSWF projects around the world, one of the most notable is Clair Ridge field in the United Kingdom. In most cases, the petroleum industry seeks to extend the economic life of existing mature fields due to the difficulty of finding new assets. In order to improve oil recovery, the waterflood scheme is generally performed as a secondary recovery process. The injected water is usually a blend of formation water and seawater resulting in very high salinity water injection. LSWF can be a promising technique to be implemented in these fields to enhance oil recovery. To define the potential, this study presents an analysis of a synthetic sandstone formation response to an LSWF process. Fractional flow theory is applied to a one-dimensional flow model to illustrate the initial idea of LSWF potential in an ideal reservoir. Then, a numerical reservoir model is built to determine this estimation of the incremental oil recovery. A sensitivity analysis study is also conducted and can be used to predict the potential of various fields based on their properties having the greatest impact on this process. At last, Monte Carlo simulation is applied in order to determine the distribution and probability of the increased oil recovery from LSWF process. The conclusions of this study show that the results due to LSWF technique depend heavily on the initial wettability of the reservoir, the starting point of the LSWF, and the initial salinity of the connate water. LSWF conducted at an oil-wet reservoir with low connate water salinity when water cut has reached 90% from conventional waterflood gives the best incremental oil recovery compared to the conventional waterflooding result itself, which is 2.25% higher. However, the potential of LSWF decreases rapidly when conditions are not met optimally and reservoirs are water-wet and have high salinity. From the result of Monte Carlo simulation, the values of incremental oil recoveryÃ‚Â’s P90 from oil-wet, mixed-wet, and weak water-wet types of reservoir are 1.35%; 0.8%; and 0.6% respectively.